Importance of Trust in the Knowledge Based Leadership - Marian NĂSTASE (Revista de Management Comparat International)
More pressures are placed on leaders' decisions in terms of assuring the survival and development of their organization. As the knowledge based economy and society proves to be more than fashionable terms, the leaders have to develop new approaches able to face the challenges of a dynamic environment.